Place Marketing, Place Branding, and Social Media: Perspectives of Municipal Practitioners. (8th December 2016) - Cleave, Evan; Arku, Godwin; Sadler, Richard; Kyeremeh, Emmanuel
Abstract: The purpose of this paper is to examine how social media is used as a promotional tool for economic development at the municipal level through place marketing and branding, to identify and explore what specific tools are being used, and to discuss the strengths and limitations of use. Primary data was collected through in‐depth interviews with 16 municipal economic development practitioners in the Province of Ontario, Canada. Additional data collected from municipal social media accounts was used to further reinforce the qualitative data and allow for triangulation and greater breadth of analysis. The findings suggest that social media is being used as a tool to promote local services and political information rather than communicate a brand position. Additionally, limited interaction with the audience reduces not only the effectiveness of place marketing efforts but also enhancement of place brands. While some findings are place specific (as study design limited research participants to municipalities in Ontario), these findings can be shared with other locales in advanced economies to provide them with information to make improvements in the way communication technology is utilised. This research paper provides a better understanding of how social media is being used by municipalities and how it fits into place marketing and place branding.